The effectiveness of virtual interactive video in comparison with online classroom in the stroke topic of theoretical neurology in COVID-19 pandemic - Alireza Vakilian; Ehsan Zare Ranjbar; Mahsa Hassanipour; Hassan Ahmadinia; Hamid Hasani (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Sufficient interaction between the trainers and the trainees in medical education is always one of the biggest challenges for an educational system. This study was designed to evaluate the effect of virtual interactions within the educational content of stroke on the effectiveness of teaching for general medicine students during COVID-19 crisis. MATERIALS AND METHODS: Eight medical students applying for stroke education were divided into two groups by simple random sampling (Rafsanjan Medical School, 2020). The first group participated in an online classroom via the Adobe Connect platform without virtual interaction. The second group used a video presentation containing interaction scenarios. The effectiveness evaluation of each type of educational content was done by comparison of the final exam scores and the results of an electronic satisfaction questionnaire in each group. Finally, using SPSS software version 18, the data were analyzed with independent samples t-test. RESULTS: This study showed that the mean of the examination scores of the interactive virtual content group (6.14 ± 1.46) was significantly higher than the online class group (4.50 ± 1.50) (P < 0.001), and also the results of satisfaction assessment showed that this group was more satisfied with their educational content (P = 0.005). CONCLUSION: Evaluation of the virtual stroke training effectiveness for general medical students shows that the educational approach of video with virtual interactions is an effective learning method in medical topics and can be considered as an efficacious educational model in online teaching.